PROFILING NUCLEAR RECEPTOR EXPRESSION IN UNDIFFERENTIATED AND DIFFERENTIATED SH-SY5Y NEUROBLASTOMA CELL LINES - Myrzagaliyeva, Arailym (Nazarbayev University School of Sciences and Humanities, 2025)
This thesis explored the differentiation of SH-SY5Y neuroblastoma cells using retinoic acid and the expression of key molecular markers associated with neuronal maturation. Morphological analysis confirmed successful differentiation, as indicated by increased neurite length and reduced cell clustering. RT-PCR revealed changes in nuclear receptor gene expression. Additionally, this study successfully expressed recombinant human growth factors (BDNF, GDNF, FGF) to develop cost-effective alternatives to commercial reagents. While FGF was predominantly found in the soluble fraction, BDNF and GDNF showed limited solubility, highlighting the need for further optimization. Overall, the findings contribute to a better understanding of SH-SY5Y differentiation and lay the foundation for future work involving enhanced differentiation protocols and the functional use of in-house-produced growth factors.
Keywords: Retinoic Acid; Neuronal Differentiation; Dopaminergic Markers; In-House Growth Factors; type of access: embargo